LITERASI DIGITAL PEMERINTAHAN SEBAGAI PERWUJUDAN ASN BERAKHLAK YANG ADAPTIF DAN KOMPETITIF - Nurdewi (Jurnal Penelitian Multidisiplin Ilmu, 2022)
Government digital literacy for state apparatus, in this case ASN (State Civil Apparatus), is the estuary of the success of public services as a whole. The industrial revolution 4.0 and towards society 5.0 creates changes in public services by adjusting digital construction in the mechanism of service delivery to the community. The development of technology is balanced with the increase in the competence of human resources in terms of digital technology capabilities. In carrying out their duties, ASN needs to have various capabilities in the field of technology adaptively with competitive advantages. This research is a qualitative research type with a phenomenological approach. The data sources used are primary data sources, namely several informants from the State Civil Apparatus (ASN) in North Maluku Province.